Pengaruh Kompetensi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Puskesmas Sialang - Susanti, Elva; Masrizal, Masrizal; Rahim, Hamidah (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
Performance is the level of individual success as a whole in a certain period when carrying out tasks, such as work standards, targets, or predetermined goals and criteria that have been mutually agreed upon. The purpose of this study was to determine the effect of competence and work environment on employee performance at the Sialang Lima Puluh Kota Health Center. This research consists of two independent variables (competence and work environment), and one dependent variable (employee performance). The data collection in this study used a questionnaire filled out by respondents, namely Sialang Health Center employees as many as 51 people. Data analysis used in this study was in the form of SPSS version 22 software. The results obtained based on SPSS data processing showed that there was a partially significant positive effect between competence on employee performance and a negative effect that was not significant between work environment on employee performance, and there was significant positive effect simultaneously between competence and work environment on employee performance at the Sialang Lima Puluh Kota health center.